Pentingnya Etika Islam - Muhammad Amin (Al-Hikmah Journal for Religious Studies, 2012)
God is the source of ethics.  He endavours human being with the reflection his attributes. It makes human being aware of the existence of The Omnipresent. The “awareness of God”brings about good ethic in human’s activity. Every activity done by human being must be relevant and related to ethics as the  base fundament of life. It is in line with the prophet’s mission that is to improve the human character to be better and civilized base on al-Quran and hadis